Aggregated Hendra virus C-protein activates the NLRP3 inflammasome to induce inflammation - Kristian Barry; Christopher Harpur; Maggie Lam; Michelle D. Tate; Ashley Mansell (BMC, 2023)
Abstract Background Hendra virus is an emerging virus with a geographically broad host reservoir. In humans, Hendra virus causes excessive inflammatory disease of the lung and nervous system. Our current understanding as to how Hendra virus or what factors induce inflammation is limited and as such, there are currently no therapeutic options available for patients who contract Hendra virus. Recent studies have identified viral aggregating proteins as drivers of inflammation in influenza A virus and SARS-CoV-2 virus. In this study, we sought to identify potential aggregating Hendra virus proteins as proof-of-concept that inflammasome activation may induce inflammation and contribute to disease pathology. Results Here, we have identified that a peptide analogue of Hendra virus C protein (termed HeVc) forms aggregates and activates the NLRP3 inflammasome through phagocytic uptake into cells in vitro. Treatment of cells with the specific NLRP3 inhibitor MCC950 ameliorated IL-1β secretion responses in vitro. Critically, in vivo intranasal inoculation of mice with aggregated HeVc peptide induced pulmonary inflammation, suggesting HeVc may drive immunopathology during infection. Importantly, mice treated with MCC950 demonstrated reduced IL-1β secretion into the bronchoalveolar space, highlighting the role of NLRP3 in host HeV infections and a potential therapeutic strategy to reduce disease pathology. Conclusion Taken together, these results identify Hendra virus C protein as a possible contributor to immunopathology during Hendra virus infections. Importantly, these studies highlight a potential role for NLRP3 in driving disease-associated inflammation, critically identifying a possible therapeutic strategy to alleviate disease-associated inflammation of infected patients through targeting of the NLRP3 inflammasome.